PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DALAM PEMBELAJARAN IPAS DI SD NEGERI 1 TONDANO - Pangalila, Natalia Gabriela; Rawis, Joulanda A. M.; Katili, Fonny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of grade IV students at SD Negeri 1 Tondano in Science and Social Sciences (IPAS). The low learning outcomes were caused by less varied learning methods, the dominance of one-way lecture methods, and the lack of active student involvement in the learning process. The purpose of this study was to improve the learning outcomes of grade IV students in IPAS learning at SD Negeri 1 Tondano through the application of the Problem Based Learning (PBL) model. This research is a Classroom Action Research (CAR) carried out in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects of the study were 18 fourth-grade students of SD Negeri 1 Tondano consisting of 13 male students and 5 female students. Data collection techniques used include observation, formative tests, and documentation, analyzed descriptively. The results showed that the implementation of the PBL model could improve student learning outcomes. In cycle I, the mastery level reached 69.8%. After improvements were made in cycle II, the value increased to 82.9%, exceeding the success indicator of 75% of students achieving KKTP. The PBL model is able to create an active, fun, and meaningful learning atmosphere, and encourages students to think critically and be actively involved in real problem solving.